Improvements in hip stability and knee muscle strength after a single-dose platelet-rich plasma injection combined with exercise in women with knee osteoarthritis - Beydagi, Muharrem Gokhan; Bagdatli, Sibel Bozgeyik; Topal, Yusuf; Kinikli, Gizem Irem; Huri, Gazi; Guney-Deniz, Hande (Springer London Ltd, 2026)
Background Knee osteoarthritis (OA) is associated with pain and lower-limb muscle weakness. Platelet-rich plasma (PRP) may reduce symptoms, but functional recovery may depend on concurrent exercise. Aims: To evaluate changes in pain and knee/hip muscle strength after a single intra-articular PRP injection combined with a 6-week home exercise programme in women with knee OA. Methods In this single-group longitudinal study, 27 women (mean age 57.5 +/- 7.3 years) performed home exercises three times weekly for 6 weeks after unilateral PRP injection. Outcomes were assessed at baseline (5 days post-injection), week 6, and week 12: hip stability isometric strength using the Hip Stability Isometric Test (HipSIT), quadriceps and hamstring strength (hand-held dynamometry; N/kg), and activity pain using a visual analog scale (VAS, 0-10). Repeated-measures ANOVA was used. Results On the affected side, The Hip Stability Isometric Test (HipSIT) increased from 2.68 +/- 1.19 to 3.15 +/- 1.13 at week 6 and 3.25 +/- 1.19 at week 12 (p=0.006). Quadriceps strength increased from 2.57 +/- 0.91 to 2.95 +/- 0.98 and 2.88 +/- 1.07 (p=0.001), and hamstring strength from 1.43 +/- 0.56 to 1.67 +/- 0.59 and 1.69 +/- 0.56 (p=0.011). Activity pain decreased from 7.27 +/- 2.10 to 4.48 +/- 2.42 and 4.22 +/- 2.93 (p=0.001). Conclusions A single PRP injection followed by a short home exercise programme was associated with reduced pain and improved hip stability and knee muscle strength up to 12 weeks in women with knee OA.
Keywords: Knee osteoarthritis; Platelet-rich plasma; Exercise therapy; Hip muscle strength; Hand-held dynamometer; Pain